Mussel-Inspired Magnetic Dissolving Pulp Fibers Toward the Adsorption and Degradation of Organic Dyes - Yang, Jiawei; Lu, Shengchang; Wu, Hui; Hu, Huichao; Miao, Qingxian; Huang, Liulian; Chen, Lihui; Ni, Yonghao (Frontiers in Chemistry, 2022)
In this work, a simple synthetic method was used to prepare a new type of magnetic dissolving pulp (MDP) @polydopamine (PDA) fibers. The hydroxyl groups of the fibers were converted into carboxyl groups after succinylation. Fe3O4 nanoparticles were grown in situ on the fibers. The prepared MDP@PDA fibers have catalytic reduction efficiency and adsorption performance for methylene blue organic dyes, and it has been thoroughly tested under various pH conditions. Fe3O4@PDA fibers have high reusability, are easy to separate, and regenerate quickly. The catalytic and adsorption efficiency barely decreases after repeated use. The surface of dissolving pulp fibers with a functionalized multifunctional PDA coating is used to create multifunctional catalysts and adsorbent materials. This study presents a very useful and convenient method for the synthesis and adjustment of MDP@PDA fibers, which have a wide range of potential applications in catalysis and wastewater treatment.